Development of a contextualised data analytics framework in South African higher education: Evolvement of teacher (teaching) analytics as an indispensable component - Janse van Vuuren, E.C. (South African Journal of Higher Education, 2020)
Data analytics in higher education aims to address, amongst other matters, student success and the factors related thereto. Faced by continuous poor student success rates, the Faculty of Economic and Management Sciences at a South African university embarked on the development and implementation of a contextualised data analytics framework to address this problem. Implementation of the framework highlighted the need for the inclusion of teaching (teacher) analytics as an integral part of the framework. Including teaching analytics not only ensured a more comprehensive understanding of the teaching and learning process, but also resulted in unexpected extensions of the framework for the scholarly development of teachers. Features of the adapted data analytics framework, with a specific focus on the teaching (teacher) analytics component, is presented in this article.